ANALISIS PEMILIHAN KAPAL TANPA AWAK DALAM OPERASI TINDAKAN PERLAWANAN RANJAU DENGAN METODE ANALYTICAL HIERARCHY PROCESS - Hariwibowo, Rendra; Rooswirawan, Avianto (AGUSPATI Research Institute, 2022)
Mine Warfare is divided into Mining Operations and Mine Countermeasure (MCM) Operations. MCM Operations are all actions taken to counter mines or neutralize sea mines. The MCM Operation is one of the tasks carried out by the vessels of the Mine Countermeasure (MCM) Squadron of Fleet Command. The vessels of the MCM Squadron currently consist of the Mine Hunting (MH) ships and the Minesweepers (MS). For Optimalize in their capabilities both in terms of platforms and sewaco which greatly affect the implementation of MCM Operations. Several countries have developed more effective technology by utilizing Unmanned Vessels equipped with equipment and sensors with MCM capabilities. Therefore, researchers consider it necessary to conduct research to select the right Unmanned Vessel for Mine Squadron of Fleet Command.